2010
DOI: 10.5194/bg-7-2339-2010
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal incorporation in foraminiferal calcite: results from multi-element enrichment culture experiments with <i>Ammonia tepida</i>

Abstract: Abstract. The incorporation of heavy metals into carbonate tests of the shallow water benthic foraminifer Ammonia tepida was investigated under controlled laboratory conditions. Temperature, salinity, and pH of the culture solutions were kept constant throughout the duration of this experiment, while trace metal concentrations were varied. Concentrations of Ni, Cu, and Mn were set 5-, 10-, and 20 times higher than levels found in natural North Sea water; for reference, a control experiment with pure filtered n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
68
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 76 publications
13
68
1
Order By: Relevance
“…Mn / Ca signatures of the ambient bottom water are recorded by benthic foraminifera. For example, culture experiments have confirmed that the species Ammonia tepida incorporates Mn into the test proportional to the concentration in the ambient water masses (Munsel et al, 2010). Thus, during benthic foraminiferal calcification under hypoxic conditions, more Mn will be assimilated into their calcite tests, whereas under anoxic conditions, or oxic conditions in particular, Mn is expected to decrease, albeit to different amounts (Pena et al, 2005).…”
Section: L Mckay Et Al: a Comparison Of Benthic Foraminiferal Mnmentioning
confidence: 91%
See 2 more Smart Citations
“…Mn / Ca signatures of the ambient bottom water are recorded by benthic foraminifera. For example, culture experiments have confirmed that the species Ammonia tepida incorporates Mn into the test proportional to the concentration in the ambient water masses (Munsel et al, 2010). Thus, during benthic foraminiferal calcification under hypoxic conditions, more Mn will be assimilated into their calcite tests, whereas under anoxic conditions, or oxic conditions in particular, Mn is expected to decrease, albeit to different amounts (Pena et al, 2005).…”
Section: L Mckay Et Al: a Comparison Of Benthic Foraminiferal Mnmentioning
confidence: 91%
“…Recent culturing experiments on benthic foraminifera demonstrate that calcification can occur even under anoxic conditions (Nardelli et al, 2014). This is key for the discussion of trace-elemental data derived from the foraminiferal tests, as not only does the timing of the calcification determine the geochemical signature, but it also shows that the signature is recorded in a wide range of oxygen conditions.…”
Section: Comparison Of Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These Mn/Ca may be used to infer changes in seawater Mn concentration due to variable terrigenous input (Klinkhammer et al, 2009). Culture studies with benthic foraminifera have shown that Mn uptake linearly relates to Mn concentration in the seawater (Munsel et al, 2010). Therefore, the observed (near) doubling in the median Mn/Ca in the inner layer thus may suggest a twofold increase in Mn concentration in the ambient seawater, likely related to enhanced terrigenous input via dust or lower sea level.…”
Section: Holocene-lgm Changesmentioning
confidence: 99%
“…Benthic foraminifera secreting calcium carbonate shells are considered to be very sensitive to the environmental conditions of the host sea water (e.g. Boyle, 1981;Wefer et al, 1999;Lea, 2004;Munsel et al, 2010). Species distribution and population densities of foraminifera are in fact used for pollution monitoring (Alve, 1991(Alve, , 1995Yanko et al, 1994Yanko et al, , 1999Debenay et al, 2001Debenay et al, , 2005Coccioni et al, 2003Coccioni et al, , 2005; Armynot du Châtelet et al, 2004;Cherchi et al, 2009;Frontalini et al, 2009;Romano et al, 2009;Frontalini and Coccioni, 2011;Denoyelle et al, 2012;Foster et al, 2012).…”
Section: A Cherchi Et Al: Bioerosion By Microbial Euendoliths In Bementioning
confidence: 99%